Przemiany polityczno-ustrojowe w Federacji Rosyjskiej w okresie pierwszej prezydentury Władimira Putina (2000-2008) – zagadnienia wybrane - Szukalski, Jerzy (Przegląd Wschodnioeuropejski, 2023)
Legal-political changes in the Russian Federation during the first presidency of Vladimir Putin, covering the years 2000-2008, are the subject of the article. The study first focuses on the strengthening of executive power, both at the central and regional levels, consolidating the power camp and shaping the political system of the state. In the period under analysis, the powers of the President of the Russian Federation were increased, the Federation Council was weakened, control over the regions was strengthened, and a number of rights and freedoms of citizens were limited. In his actions, Putin relied on the power ministries and secured the loyalty of the State Duma and the oligarchs. The United Russia party became his political base. Putin’s political opponents and competitors were ruthlessly eliminated from political life. An analysis of the features of the political system of the Russian Federation indicates that it had become an authoritarian state.